Recombinant mouse interferon-gamma regulation of antibody production. - Johnson, H M (1983)
Interferon-gamma produced in monkey cells by transfection with mouse interferon-gamma cDNA suppressed the mouse in vitro antibody response in a manner similar to that of natural mouse interferon-gamma. Significant suppression was obtained with as little as 1 U of interferon. Recombinant human interferon-gamma produced by cloning in a similar fashion was not suppressive. Both the suppressive and the antiviral activities of recombinant interferon-gamma were neutralized by antibodies to mouse natural interferon-gamma. Thus, interferon-gamma was responsible for the immunosuppression. At the cellular level, the recombinant interferon-gamma was capable of activating macrophages to suppress antibody production. The data provide clear-cut evidence that interferon-gamma plays an important role in regulation of immunological processes.